Contrast-enhanced CMR in patients after percutaneous closure of the left atrial appendage: a pilot study - Mohrs, Oliver K.; Wunderlich, Nina; Petersen, Steffen E.; Pottmeyer, Anselm; Kauczor, Hans-Ulrich (Journal of cardiovascular magnetic resonance, 2011)
To evaluate the feasibility and value of first-pass contrast-enhanced dynamic and post-contrast 3D CMR in patients after transcatheter occlusion of left atrial appendage (LAA) to identify incorrect placement and persistent leaks.